Pengaruh Kualitas Produk Dan Promosi Terhadap Minat Beli Ulang Produk Jamur Tiram Di SMK Negeri 1 Samalantan - Priti Sera; Blasius Manggu (Transformasi: Journal of Economics and Business Management, 2023)
Mold oyster is one _ product growing agriculture _ in demand by consumers Because mark nutrition and deliciousness. Study This aim For analyze influence quality products and promotions to interest buy repeat mold oysters _ Study This use method survey with spread questionnaire to consumer mold oysters in various regions. Collected data analyzed use method statistics descriptive and multiple linear regression Analysis results show that quality product own influence significant to interest buy repeat consumer mold oysters _ Promotion own influence positive to interest buy repeat mold oysters. Findings study This give implication practical for producer mold oyster in increase interest buy repeat consumer. Producer need focus on effort enhancement quality product, incl use technique good cultivation, selection _ material quality raw materials, and attractive packaging. Besides that, manufacturers also have to pay attention to an effective promotion strategy For communicate superiority product to consumer. Studies it also delivers donation theoretical with confirm that quality products and promotions play role important in influence interest buy repeat consumer. Study furthermore can involve variable else, like price and image brand, for expand understanding about influencing factors _ interest buy repeat in context product agriculture other.